Debt stabilization and macroeconomic volatility in monetary unions under heterogeneous sovereign risk perceptions - Christian R. Proa\~no; Benjamin Lojak (Bamberg University, Bamberg Economic Research Group (BERG), 2015)
This paper studies the dynamics of sovereign risk, fiscal policy and the macroeconomy in a two-country monetary union framework under the assumption of a heterogeneous perception of the determinants of sovereign risk by the government and the market participants. The macroeconomic volatility resulting from various types of fiscal policy rules aimed at the stabilization of sovereign debt are investigated through numerical simulations. Among other things, these simulations show that an extreme focus on debt stabilization can be counterproductive if the financial markets care more about the country's output gap.
Keywords: 330; behavioral macroeconomics; sovereign risk; fiscal policy rules; monetary unions; macroeconomic stability